IMPLEMENTASI METODE PEMBELAJARAN BLENDED LEARNING ERA COVID 19 DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN FIQIH DI MTs AL-HUDA SUKOREJO BANYUWANGI - Anis Fauzi; Muhamad Akhsin Yusuf (MUMTAZ : Jurnal Pendidikan Agama Islam, 2022)
In the situation of the Covid 19 pandemic, many impacts occur in the community, one of which is in the realm of education that causes a decrease in students' learning interest in MTs Al-Huda sukorejo. The problem becomes a challenge for a teacher in carrying out his duties as a facilitator in the teaching and learning process, namely about how the teaching and learning process can be carried out even with the circumstances of the Covid 19 pandemic. Therefore, teachers need to think about innovation by utilizing online media as an alternative way of implementing the teaching and learning process, but online or distance learning does not guarantee that it can trigger students' learning interest in learning, because somehow in the subjects it takes practice, especially in the subjects fiqh hajj and umrah materials. With the chronology presented above, the teacher concludes one of the effective learning methods to increase students' learning interest is to combine learning is the Blended Learning method.